Organoleptic Quality of Dried Candied Siwalan Fruit (Borassus Flabellifer L.) - Yasa, I Made Murna; Kristiana, Nina Indra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study includes innovation of new processed products and utilization of siwalan fruit processed into dry sweets because it has a fairly long shelf life. This study aims to determine the quality of dry sweets made from siwalan fruit preserved by sugaring and drying. The data collection methods used are experimental test methods, organoleptic tests, panelists, documentation, questionnaires, and Likert scales. This study was assessed by organoleptic tests tested on panelists to determine the quality of dry sweets made from siwalan fruit seen from the taste aspect getting an index value of 95%, from the color aspect getting an index value of 87%, from the aroma aspect getting an index value of 88%, and from the texture aspect getting an index value of 90%, thus getting a total average result of 90% with very good interpretation criteria.